2007
DOI: 10.1111/j.1365-2672.2006.03263.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Laribacter hongkongensis, a novel bacterium associated with gastroenteritis, from drinking water reservoirs in Hong Kong

Abstract: Aims:  Freshwater fish has been found to be the reservoir of Laribacter hongkongensis, a recently discovered bacterium associated with community‐acquired gastroenteritis. However, little is known about the ecology of this bacterium in the aquatic environment. We carried out a surveillance study to investigate the presence of L. hongkongensis in water and freshwater fish from 10 drinking water reservoirs in Hong Kong. Methods and Results:  Using membrane filtration, L. hongkongensis was isolated from the waters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…7,10 To extract bacterial DNA, 80 µL of 0.05 M NaOH were added to 20 µL of bacterial cells suspended in distilled water, and the mixture was incubated at 60 °C for 45 min, followed by the addition of 6 µL of Tris-HCl (pH 7.0), achieving a final pH of 8.0. The resultant mixture was diluted ×100, and 5 µL of the diluted extract was used for polymerase chain reaction (PCR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10 To extract bacterial DNA, 80 µL of 0.05 M NaOH were added to 20 µL of bacterial cells suspended in distilled water, and the mixture was incubated at 60 °C for 45 min, followed by the addition of 6 µL of Tris-HCl (pH 7.0), achieving a final pH of 8.0. The resultant mixture was diluted ×100, and 5 µL of the diluted extract was used for polymerase chain reaction (PCR).…”
Section: Methodsmentioning
confidence: 99%
“…2,8 This species has also been isolated from drinking water reservoirs, Chinese tiger frogs and little egrets. 9,10,11 Pulsed-field gel electrophoresis and multilocus sequence typing (MLST) demonstrated that the fish and patient isolates fall into separate clusters, suggesting that some clones could be more virulent or adapted to humans. 8,12 The complete genome of L. hongkongensis was recently sequenced, and this bacterium's mechanism of acid resistance was characterized.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the easy access to clinical specimens, the oral cavity and the gastrointestinal tract are the most important sources for bacterial discovery in humans Woo, Tse, Lau, et al, 2005;Woo, Wong, et al, 2010;Woo et al, 2014;Yuen et al, 2001). The use of 16S rRNA gene sequencing for detection has also facilitated downstream studies of these novel bacteria to help understand their disease associations, pathogenicity, transmission routes and potential reservoir(s) (Couturier, Slechta, Goulston, Fisher, & Hanson, 2012;Curreem et al, 2011;Elsendoorn, Robert, Culos, Roblot, & Burucoa, 2011;Faibis et al, 2008;Kim et al, 2011;Lau, Fan, et al, 2012Lau et al, 2005Lau et al, , 2009Lau, McNabb, et al, 2007;Lau, Wong, Li, Woo, & Yuen, 2008;Lau, Woo, Fan, Lee, et al, 2007;Lau, Woo, Fan, Ma, et al, 2007;Lau, Woo, Hui, et al, 2003;Ni et al, 2007;Smith, Pandey, & Ussher, 2012;Tang et al, 2013;Teng, Huang, et al, 2014;Teng et al, 2005;Uckay et al, 2007;Woo, Kuhnert, et al, 2003;Woo, Lau, Teng, & Yuen, 2005;Woo, Ma, et al, 2005Woo, Tam, et al, 2002;Woo, Teng, Lau, & Yuen, 2006;Woo, Teng, et al, 2004Woo, Wong, et al, 2010;Woo et al, 2014;Xiong et al, 2014;Yuen et al, 2001).…”
Section: S Rrna Gene Sequencing For Bacterial Discoverymentioning
confidence: 97%
“…L. hongkongensis is a recently discovered β-Proteobacterium that is associated with community-acquired gasteroenteritis and traveler's diarrhea (Yuen et al, 2001;Woo et al, 2004;Woo et al, 2005). It can inhabit in the intestines of freshwater fish, frogs and humans, and can also grow independently in freshwater environments (Woo et al, 2004;Teng et al, 2005;Lau et al, 2007;Ni et al, 2007;Lau et al, 2009). Therefore it needs to cope with varying environmental temperatures in these different growth habitats.…”
Section: Differential Proteomicsmentioning
confidence: 99%